An Altercentric Perspective on the Origins of Brokerage in Social Networks: How Perceived Empathy Moderates the Self-Monitoring Effect - Kleinbaum, Adam M.; Jordan, Alexander H.; Audia, Pino G. (Organization Science, 2015)
Social structure matters in organizational life, but our understanding of the origins of social network structure remains limited. In this paper, we observe that the literature on individual differences and social networks focuses almost exclusively on ego’s views of herself and of her network. Our approach complements this egocentric perspective with a more altercentric view, in which others’ perceptions of and reactions to ego’s personality and relational behavior shape the structure of ego’s network. Our altercentric perspective builds on earlier evidence that the construct of self-monitoring is associated with brokerage, but it suggests that the effect of self-monitoring on brokerage is amplified in those perceived as highly empathic and attenuated in those perceived as lower in empathy. A mechanism that underlies this effect is the greater propensity of others to reciprocate the social interactions of high-empathy, high self-monitors than those low in empathy. We find support for these predictions in a study of the dynamic emergence of a social network among a complete cohort of MBA students and conclude that alters are active agents in the formation of ego’s network.